2019
DOI: 10.1111/jocn.14952
|View full text |Cite
|
Sign up to set email alerts
|

Staff responses to residents exposing their genitals in public in long‐term care settings: The gap between common and perceived best practices

Abstract: Aims and objectives To explore staff reactions to residents’ behaviour consisting in exposing their genitals in public, and to differentiate between what is perceived as common practice (what most staff do) and best practice (the best possible approach). Background The presence of inappropriate sexual behaviours (ISBs) in long‐term care facilities poses practical and ethical dilemmas since they may impinge on the rights of others (staff and residents) and thus need to be adequately monitored and managed. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Various dominant discourses (e.g., biomedical approach, ageism, ableism, and heterosexism) have intersected to culminate in a culture that places limits on sexual freedoms in the guise of protection of individual’s safety and/or organizational liability. Frequent responses to sexual expression in LTC are to remove, restrain, or reprimand rather than take a supportive, proactive approach, such as providing sex education and access to sexual privacy (Barmon et al, 2017; Villar et al, 2019b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various dominant discourses (e.g., biomedical approach, ageism, ableism, and heterosexism) have intersected to culminate in a culture that places limits on sexual freedoms in the guise of protection of individual’s safety and/or organizational liability. Frequent responses to sexual expression in LTC are to remove, restrain, or reprimand rather than take a supportive, proactive approach, such as providing sex education and access to sexual privacy (Barmon et al, 2017; Villar et al, 2019b).…”
Section: Resultsmentioning
confidence: 99%
“…An associated policy problem is the moral distress, discomfort, and dissatisfaction for HCP caused by sexual situations in the workplace (Cook et al, 2017; Srinivasan et al, 2019; Villar et al, 2019b). These sexual situations range from having to talk about sexual issues with residents to dealing with disinhibited sexual behavior or sexual advances (Villar et al, 2019a).…”
Section: Resultsmentioning
confidence: 99%
“…In several instances, sexual expressions that contained erotic or more explicit elements were subject to more severe condemnation [35,55] than expressions of tenderness. Many of the most common sexual expressions among the residents, such as masturbation, kissing, and intercourse, were also the ones that staf found most discomforting [40,52,62].…”
Section: Hollow Attitudesmentioning
confidence: 98%
“…Masturbation was one of the most common sexual expressions among the residents and one that staf most believed the residents needed to be satisfed [52,59,61,64]. Despite this, masturbation was also one of the sexual expressions that created the most discomfort among staf [54,62]. Villar et al [54] found that staf saw masturbation in the RAC as an unexpected event, and they did not know how to react.…”
Section: Hollow Attitudesmentioning
confidence: 99%
“…what they actually do) and best practice (how members of staff think apathy in PLWD should be ideally managed). As reported in other areas of intervention with PLWD involving communication 40 or sexual behaviors 41 , if differences between common and best practices are great, the gap would indicate that there are barriers preventing staff from dealing with apathy in the way they should.…”
Section: Managing Apathy In Institutional Settingsmentioning
confidence: 99%